Time and Digital Poetics - Julio Pinto (tripleC: Communication, Capitalism & Critique)
From a semiotic standpoint, this discussion focuses on the issue of time in digital environments so as to attempt an answer to the question whether temporal awareness undergoes a collapse into presentness or whether narrative structure is dissolved in the unpredictability of links that may be accessed randomly; that is, the hypertext loses exactly the anaphoric reference to a significant preexistence on behalf of a succession of bits of presentness.